Performance analysis of Unsignal Intersection and Road section with MKJI Method 1997 - Muhammad Isradi; Enif Asfarianto Pratama (NAROTAMA UNIVERSITY, Indonesia)
Intersection Telkom Jatiasih is one of the congestion point in Bekasi City. This is at leave because of the high volume of traffic and also a busy route from Bekasi to Jakarta and the surrounding area, plus the direction to the toll gate Jatiasih. There is no sign – traffic sign making of Intersection Telkom Jatiasih is an unsignable junction, this is what causes the flow of irregular vehicles causing congestion. The data retrieval method is done by surveying directly to the research site. Based on survey result in Telkom Jatiasih intersection, the highest vehicle volume accurred in the afternoon of Monday, April 29 th, 2019. Calculated results based on the field survey result data using the MKJI 1997 book guidelines, obtaining the Degree of Saturation (DS) = 1,86 with the Level Of Service F value, indicating the stopping of the vehicle current at the congestion point such as the meeting path, or repair lanes that cause a long queue of vehicles. On the road Of Wibawa Mukti II Highway – Jatiasihi the vehicle flows are still recorded stably with the Degree of Saturation (DS) = 1,16 with a Level Of Service F value which means the level of road service is still stable. From the research results get an alternative solution Telkom Jatiasih intersection is in alternative 2 because it gets a decrease in the Degree of Saturation (DS) = 1,11 with the value of the Level Of Service F which means high traffic flow condition, but Current conditions are still stable.